The Fascist persuasion in radical politics - Gregor, A. James (Anthony James), 1929- (Princeton University Press, 1974)
How valid are the assertions of contemporary radicals who insist that they are "Marxists"? A. James Gregor measures the distance that separates today's radicals from the belief system of Marx and Engels. He finds that the characteristic qualities of modern mass-mobilizing movements bear more impressive similarities to the paradigmatic Fascism of Benito Mussolini than to "classical Marxism." Thus he offers a new conceptual framework for the analysis of contemporary totalitarian movements and established regimes.Originally published in 1974.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Fascism.; Radicalism.; Socialism.; Fascisme.; Radicalisme.; fascism.; radicalism.; POLITICAL SCIENCE -- Political Ideologies -- Fascism & Totalitarianism.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Fascism; Radicalism; Socialism